Innovations and technology disruptions in the food sector within the COVID-19 pandemic and post-lockdown era. (April 2021) - Galanakis, Charis M.; Rizou, Myrto; Aldawoud, Turki M.S.; Ucak, Ilknur; Rowan, Neil J.
Abstract: Background: COVID-19 pandemic has caused a global lockdown that has abruptly shut down core businesses and caused a worldwide recession. The forecast for a smooth transition for the agri-food and drink industry is, at best, alarming. Given that COVID-19 shutdown multiple core services (such as aviation, food services, supply chains, and export and import markets), there is an enormous deficiency in critical information to inform priority decision making for companies where this uncertainly is likely to impact negatively upon recovery. Scope and approach: The current article investigates potential innovations within the era of the COVID-19 crisis after framing them within the four issues of the food sector (food safety, bioactive food compounds, food security, and sustainability) that are directly affected by the pandemic. The prospect of foreseen innovations to disrupt the food sector during lockdown periods and the post-COVID-19 era is also discussed. Key findings and conclusions: Internet and Communication Technologies, blockchain in the food supply chain and other Industry 4.0 applications, as well as approaches that redefine the way we consume food (e.g., lab-grown meat, plant-based alternatives of meat, and valorization of a vast range of bioresources), are the innovations with the highest potential in the new era. There is also an equally pressing need to exploit social marketing to understand attitudes, perceptions, and barriers that influence the behavior change of consumers and the agri-food industry. Subsequently, this change will contribute to adapting to new norms forged by the COVID-19 pandemic, where there is a significant gap in knowledge for decision making. Highlights: Innovations within the era of the COVID-19 crisis are investigated. The prospect of innovations to disrupt the food sector during lockdowns, and post-COVID-19 era is discussed. Industry 4.0 applications, and new food consumption approaches are the innovations with the highest potential. Understanding the behavioral change of consumers and the agri-food industry is critical. This change will contribute to adapting to new norms forged by the COVID-19 pandemic.